Using mixed-method approaches to provide new insights into media coverage of femicide - Brodie, Nechama R. (My University, 2019)
South Africa has a femicide rate that is six times the world average. Over 2,500 women aged 14 years or older are murdered every year, the majority of these women killed by an intimate partner. Despite the prevalence of femicide, less than 20% of these murders are ever reported in South African news media. Studies on news-media coverage of femicide reveal a subjective and obscure process of media selection and exclusion, which contribute to an archive of crime reporting that is not reflective of actual crime rates and which actively distort the nature and frequency of certain types of crime. This influences public perceptions and fear of violent crime, including notions of who is a suspect and who is most at risk. This study uses mixed-method approaches to document and analyse the content and extent of commercial news media coverage of femicides that took place in South Africa during the 2012/2013 crime reporting year, through an original media database listing 408 femicide victims associated with 5,778 press articles. Victim and incident information is compared with epidemiological and statistical data, including mortuary-based studies and police crime statistics. Media data is explored through various media effects models, including a mixedmethods framing analysis, and is also examined by title, and by language. These analyses reveal how media constructs and depicts particular notions of gender, violence, race, and crime in South Africa.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2019
Keywords: Mixed-method study; Crime against women; Violence against women; Femicide; South Africa; SDG-5: Gender equality